2010
DOI: 10.1055/s-0029-1241030
|View full text |Cite
|
Sign up to set email alerts
|

Reproduzierbarkeit Doppler-sonografischer Messungen der fetalen Zerebralvenen: Eine Studie am Sinus transversus

Abstract: Einführung ! Der zerebrale Blutkreislauf des Fetus wird durch viele Faktoren beeinflusst. In der Autoregulation spielt unter anderem der pO 2 -und der pCO 2 -, pHWert und Blutdruck eine entscheidende Rolle [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…However, the pulsatility pattern in the intracerebral venous system can often be very variable, which makes a reliable diagnostic application difficult. A recent study on Doppler examination of the transverse sinus flow revealed that flow velocity waveforms show variations and can be either non-pulsatile, monophasic or biphasic, which significantly limits its clinical use [15].…”
Section: Spectral Doppler Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the pulsatility pattern in the intracerebral venous system can often be very variable, which makes a reliable diagnostic application difficult. A recent study on Doppler examination of the transverse sinus flow revealed that flow velocity waveforms show variations and can be either non-pulsatile, monophasic or biphasic, which significantly limits its clinical use [15].…”
Section: Spectral Doppler Studiesmentioning
confidence: 99%
“…Das Pulsatilitätsmuster in den intrazerebralen Venen kann aber oft sehr variabel sein, was eine zuverlässige diagnostische Anwendung erschwert. Eine kürzlich durchgeführte Studie zur Doppleruntersuchung des Sinus transversus zeigte, dass das Blutflussmuster Variationen aufweist und entweder nicht pulsatil, monophasisch oder biphasisch sein kann, was den klinischen Einsatz deutlich einschränkt [15].…”
Section: Spektraldopplerstudienunclassified